Engineered stem cell exosomes for oral and maxillofacial wound healing - Hao, Ming; Duan, MengNa; Yang, Zhijing; Zhou, Hengzong; Li, Shuangji; Xiang, Jingcheng; Wu, Han; Liu, Huimin; Chang, Lu; Wang, Dongxu; Liu, Weiwei (Frontiers in Bioengineering and Biotechnology, 2022)
Wound healing of the oral and maxillofacial area affects the quality of life and mental health of the patient; therefore, effective therapies are required to promote wound healing. However, traditional treatment methods have limited efficacy. Exosomes secreted by stem cells used for oral and maxillofacial wound healing have shown outstanding results. Stem cell-derived exosomes possess the regenerative and repair ability of stem cells. Moreover, they are nontumorigenic and have good biosafety. However, the application of natural stem cell exosomes is limited owing to their low yield, impurity, lack of targeting, and low drug delivery rate. Many modification methods have been developed to engineered stem cell exosomes with beneficial properties, such as modifying parent cells and directly processing stem cell exosomes. These methods include coincubation, genetic engineering, electroporation, ultrasound, and artificial synthesis of engineered stem cell exosomes. These engineered stem cell exosomes can cargo nucleic acids, proteins, and small molecules. This gives them anti-inflammatory and cell proliferation regulatory abilities and enables the targeted promotion of efficient soft tissue repair after trauma. Engineered stem cell exosomes can decrease inflammation, promote fibroblast proliferation, and angiogenesis, and decrease scar formation to promote oral and maxillofacial wound healing, including diabetic and burn wounds. Thus, engineered stem cell exosomes are an effective treatment that has the potential for oral and maxillofacial wound healing.